NILAI TAMBAH DARI USAHA PENGOLAHAN TEPUNG TERIGU MENJADI MARTABAK MARKOBAR KOTA MANADO - Amar ., nfn; Tommy F. Lolowang; Nordy F. L. Waney (Sam Ratulangi University, 2018)
This study aims to determine the magnitude: (1) the added value of flour business into martabak Markobar Manado (2) profit from flour processing business into martabak Markobar Manado City. The study was conducted in October to December 2017, located in Markobar Kota Manado. Data collection method is done by using primary data. Primary data was obtained through interviews with relevant parties based on a prepared list of questions, as well as on-site observations. Data analysis in this study using: 1) value-added analysis and 2) profit analysis with the formula Ï€ = TR - TC. The results showed that Markobar Manado process 3 types of martabak martabak 2 flavors, martabak 4 flavors and martabak 8 flavors. Number of martabak 2 taste processed ie 96 pieces with selling price per fruit of Rp. 50,000 so the total revenue is Rp.4.800.000. Number of martabak 4 flavors processed ie 144 fruit with the selling price per fruit of Rp. 80,000 so that the revenue received by Markobar is Rp.11.520.000. Number of martabak 8 taste processed ie 240 fruit with selling price per fruit of Rp. 100.00.000 so that the revenue received by Markobar is Rp.24.000.000 Profit business martabak 2 taste of Rp. 485,116.71, business profit martabak 4 taste of Rp. 5,297,675.07 and business profit martabak 8 taste of Rp. 9,322,791.78. Processing business martabak 2 flavors produce value added Rp 2,357,116.71, processing martabak 4 flavors produce value added Rp. 8,105,675.07 and martabak processing 8 flavors produce added value of Rp. 14,002,791.78.*eprm*.